Excess Mortality of Alcohol‐Dependent Individuals After 14 Years and Mortality Predictors Based on Treatment Participation and Severity of Alcohol Dependence. (16th October 2012) - John, Ulrich; Rumpf, Hans‐Jürgen; Bischof, Gallus; Hapke, Ulfert; Hanke, Monika; Meyer, Christian
<x xml:space="preserve">Abstract</x> Background Little is known about excess mortality and its predictors among alcohol‐dependent individuals in the general population. We sought to estimate excess mortality and to determine whether alcohol dependence treatment utilization, alcohol dependence severity, alcohol‐related problems, and self‐rated health may predict mortality over 14 years. Methods A random sample of the general population between the ages of 18 and 64 in 1 region in Germany was drawn. Among 4, 070 respondents with valid data, 153 alcohol‐dependent individuals were identified. For 149 of these 153, vital status information was provided 14 years later. Baseline data from the Composite International Diagnostic Interview (German version M‐CIDI) included a diagnosis of alcohol dependence according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM‐IV) of the American Psychiatric Association, alcohol dependence treatment utilization, alcohol dependence severity based on the number of DSM‐IV alcohol dependence diagnostic criteria fulfilled and a symptom frequency questionnaire, alcohol‐related problems, self‐rated general health, cigarettes smoked per day, and the number of psychiatric disorders according to the DSM‐IV at baseline. Results Annualized death rates were 4.6‐fold higher for women and 1.9‐fold higher for men compared to the age‐ and sex‐specific general population. Having participated in inpatient specialized alcohol dependence treatment was not related with longer survival than not having taken part in the treatment. Utilization of inpatient detoxification treatment predicted the hazard rate ratio of mortality (unadjusted: 4.2, 90% confidence interval 1.8 to 9.8). The severity of alcohol dependence was associated with the use of detoxification treatment. Alcohol‐related problems and poor self‐rated health predicted mortality. Conclusions According to the high excess mortality, a particular focus should be placed on women. Inpatient specialized alcohol dependence treatment did not seem to have a sufficient protective effect against dying prematurely. Having been in detoxification treatment only, the severity of alcohol dependence, alcohol‐related problems, and self‐rated health may be predictors of time‐to‐death among this general population sample.